2001
DOI: 10.1097/00005537-200112000-00008
|View full text |Cite
|
Sign up to set email alerts
|

A Computer‐Assisted Anatomical Study of the Nasofrontal Region

Abstract: The frontal sinus opens into the middle meatus medial to the uncinate process in 88% of the patients and lateral to the uncinate process in 12% of the patients. The naturally wide dimensions of the frontal ostium help to explain why postoperative patency can be achieved merely by exposing the ostium without the need to enlarge it. The frontal ostium dimensions in one side may differ considerably from the contralateral side. An agger nasi cell or a terminal recess, or both, are found in most cases. Image-guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
136
5
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 15 publications
(24 reference statements)
3
136
5
4
Order By: Relevance
“…In the literature distribution of agger nasi cells are between 78 and 98.5 % of the patients. According to Landsberg and Friedman [13] agger nasi cells were found in 78 % of scans. Bolger et al [14] has found the prevalence in 98.5 % of their cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the literature distribution of agger nasi cells are between 78 and 98.5 % of the patients. According to Landsberg and Friedman [13] agger nasi cells were found in 78 % of scans. Bolger et al [14] has found the prevalence in 98.5 % of their cases.…”
Section: Discussionmentioning
confidence: 95%
“…In our study the superior attachment of the uncinate process to lamina papyraceae was 82 %, to middle turbinate was 4 % and to the skull base was 14 %. According to Landsberg and Friedman [13], the uncinate process main superior attachment onto the surrounding structures was found to have the following distribution; 52 % to the lamina papyraceae, 18.5 % to posteromedial wall of agger nasi cell, 17.5 % to the lamina paparaceae and the junction of the middle turbinate with the cribriform plate, 3.6 % to ethmoid roof and 1.4 % to the middle turbinate. In a study in Taiwanese population, Liu et al [17] had found that single insertion of the uncinate process onto the lamina papyraceae was the most common type (70.4 %) as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Its tip lies sagittal and has a close relationship with the agger nasi cell, middle turbinate, lamina papyracea, and anterior skull base. Using coronary CT, Landsberg 6 divided the attachment of the uncinate process Table 1 The complication ratio of the patient AB, anterior ethmoid artery bleeding; EE, eyelid ecchymosis; EFMT, endoscopic frontal sinus surgery with the help of minitrephination; FAEB, frontal sinus surgery in the route anterior to the ethmoid bulla; LI, lacrimal injury; LPI, lamella papyrace injury; MELP, modified endoscopic Lothrop procedure. into 6 pattern types.…”
Section: Discussionmentioning
confidence: 99%
“…The frontal sinus patency can be achieved by merely exposing the natural sinus ostium with only a rare need to enlarge it [14]. This procedure usually has the superior attachment of uncinate process and suprainfundibular plates as the most important landmarks [4,15,16]. However, the anatomical structures and landmarks can be compromised by severe polypoid lesions in anterior ethmoid sinus or by previous surgery or by postoperative scarring.…”
Section: Discussionmentioning
confidence: 99%